2013
DOI: 10.1007/s00709-013-0488-9
|View full text |Cite
|
Sign up to set email alerts
|

CEP proteins: the knights of centrosome dynasty

Abstract: Centrosome forms the backbone of cell cycle progression mechanism. Recent debates have occurred regarding the essentiality of centrosome in cell cycle regulation. CEP family protein is the active component of centrosome and plays a vital role in centriole biogenesis and cell cycle progression control. A total of 31 proteins have been categorized into CEP family protein category and many more are under candidate evaluation. Furthermore, by the recent advancements in genomics and proteomics researches, several n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
70
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 83 publications
(70 citation statements)
references
References 114 publications
0
70
0
Order By: Relevance
“…CEP250 encodes the C-Nap1 protein which belongs to the CEP family of proteins,35 including over 30 proteins that form the active component of centrosome and play a vital role in centriole biogenesis, centrosome cohesion and cell cycle progression control 36. C-Nap1 dissociates from spindle poles during mitosis, but reaccumulates at centrosomes at the end of cell division and was shown to be required for cell cycle-regulated centrosome cohesion 37.…”
Section: Discussionmentioning
confidence: 99%
“…CEP250 encodes the C-Nap1 protein which belongs to the CEP family of proteins,35 including over 30 proteins that form the active component of centrosome and play a vital role in centriole biogenesis, centrosome cohesion and cell cycle progression control 36. C-Nap1 dissociates from spindle poles during mitosis, but reaccumulates at centrosomes at the end of cell division and was shown to be required for cell cycle-regulated centrosome cohesion 37.…”
Section: Discussionmentioning
confidence: 99%
“…This relationship has motivated intense efforts to elaborate the composition and mechanism of action of core DNA repair machinery as well as peripheral molecular systems that modulate this machinery to suppress genomic instability (2)(3)(4)(5). With respect to the latter, emerging evidence implicates multiple regulatory layers that link activation of the DNA damage response (DDR), repair pathway choice, and resolution of the DDR to chromatin organization (6)(7)(8)(9), RNA metabolism (10,11), and autophagy (12)(13)(14).…”
mentioning
confidence: 99%
“…For example, mutations of Cep290, known as BBS14 or KIAA0373, are observed in ciliopathies which are a group of diseases associated with ciliary dysfunction such as retinal degeneration, Joubert syndrome type 5, and Bardet-Biedl syndrome type 14 (BBS14) [11]. Cep290 is a satellite protein that localizes at the transition zone between basal body and cilia [8]. Recently, it has been reported that Cep290 plays a role in the ciliary transport process and is associated with several satellite proteins.…”
Section: Introductionmentioning
confidence: 99%
“…CEP family proteins are components of centrosome and essential for cell division. These proteins primarily control centriole duplication, MTkinetochore (KT) assembly, bipolarity, and mitotic progression [8]. Thirty-one CEP proteins have been identified and many of them are being evaluation.…”
Section: Introductionmentioning
confidence: 99%